QSO Hosts and Their Environments 2001
DOI: 10.1007/978-1-4615-0695-9_16
|View full text |Cite
|
Sign up to set email alerts
|

Near-Infrared Imaging of Steep Spectrum Radio Quasars

Abstract: We present the results of a high resolution (0.27 ′′ px −1 ) near-infrared H band (1.65 µm) imaging survey of a complete sample of 20 flat radio spectrum quasars (FSRQ) extracted from the 2Jy catalogue of radio sources (Wall & Peacock 1985). The observed objects are intrinsically luminous with median M(B) = -25.5. The median redshift of the objects in the sample is z = 0.65. At this redshift, the H band observations probe the old stellar population of the hosts at rest frame wavelength of ∼1 µm.We are able to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
29
1

Year Published

2001
2001
2005
2005

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(36 citation statements)
references
References 80 publications
(159 reference statements)
6
29
1
Order By: Relevance
“…Compared to a present-day field galaxy with a Schechter magnitude of M * R = −20.9 (Lin et al 1996), the mean values found for the hosts correspond to ∼10 L * , similar to the values found in other intermediate redshift studies (5−12 L * , Hooper et al 1997;Kotilainen et al 1998;Kotilainen & Falomo 2000). The difference in mean magnitude between radio-loud and radio-quiet hosts is quite small and less than 1σ (but in the case of I band 2σ).…”
Section: Mean Magnitudessupporting
confidence: 87%
See 2 more Smart Citations
“…Compared to a present-day field galaxy with a Schechter magnitude of M * R = −20.9 (Lin et al 1996), the mean values found for the hosts correspond to ∼10 L * , similar to the values found in other intermediate redshift studies (5−12 L * , Hooper et al 1997;Kotilainen et al 1998;Kotilainen & Falomo 2000). The difference in mean magnitude between radio-loud and radio-quiet hosts is quite small and less than 1σ (but in the case of I band 2σ).…”
Section: Mean Magnitudessupporting
confidence: 87%
“…When turning to redshifts >0.5 but lower than unity, very few observations of radio-quiet host galaxies exist. The mean magnitudes of radio-loud hosts have grown brighter by < ∼ 0.5 mag; Márquez et al (1999) find a mean of −23.0 ± 0.4, while Kotilainen et al (1998) derive a mean of −23.1 ± 0.5 for FS host galaxies and −23.6 ± 0.3 for SS hosts (Kotilainen & Falomo 2000), where quoted magnitudes have been recomputed to the R band and the cosmology of this paper.…”
Section: Mean Magnitudesmentioning
confidence: 78%
See 1 more Smart Citation
“…Extended nebulosities around quasars were investigated by several groups using various facilities from the ground (e.g., Hutchings, Janson, & Neff 1989;Veron-Cetty & Woltjer 1990;McLeod & Rieke 1995;Taylor et al 1996;Kotilainen & Falomo 2000). Altogether, these works have confirmed the presence of the host galaxies.…”
Section: Introductionmentioning
confidence: 96%
“…As well as the redshifts above 1, I have selected host galaxy measurements over the redshift range below 1 to cover the redshift range down to the well-studied low redshift QSOs (Kotilainen et al 1998, Kotilainen andFalomo 2000) . The diagrams show the result, attempting to be comprehensive at higher redshifts, while selecting quantities derived with reliable methods and good data.…”
Section: Host Galaxy Detectionmentioning
confidence: 99%